miR-638 promotes melanoma metastasis and protects melanoma cells from apoptosis and autophagy - Bhattacharya, Animesh; Schmitz, Ulf; Raatz, Yvonne; Schoenherr, Madeleine; Kottek, Tina; Schauer, Marianne; Franz, Sandra; Saalbach, Anja; Anderegg, Ulf; Wolkenhauer, Olaf; Schadendorf, Dirk; Simon, Jan C.; et al. (Oncotarget, 2015)
The present study identified miR-638 as one of the most significantly overexpressed miRNAs in metastatic lesions of melanomas compared with primary melanomas. miR-638 enhanced the tumorigenic properties of melanoma cells in vitro and lung colonization in vivo. mRNA expression profiling identified new candidate genes including TP53INP2 as miR-638 targets, the majority of which are involved in p53 signalling. Overexpression of TP53INP2 severely attenuated proliferative and invasive capacity of melanoma cells which was reversed by miR-638. Depletion of miR-638 stimulated expression of p53 and p53 downstream target genes and induced apoptosis and autophagy. miR-638 promoter analysis identified the miR-638 target transcription factor associated protein 2? (TFAP2A/AP-2?) as a direct negative regulator of miR-638, suggestive for a double-negative regulatory feedback loop. Taken together, miR-638 supports melanoma progression and suppresses p53-mediated apoptosis pathways, autophagy and expression of the transcriptional repressor TFAP2A/AP-2?.
EVALuna2:19520